Effects of Inorganic Mercury on the Conformation and Activity of Glutathione S-transferase from Schistosoma japonicum - Huang, Xin-He; Huang, Yu; Gao, Hai-Liang; Yan, Jun-Xi; Du, Lin-Fang (Asian Journal of Chemistry, 2010)
Glutathione S-transferases (GST) are a family of cytosolic or membrane-bound multifunctional enzymes present in all organisms with their main function in the detoxification of harmful physiological and xenobiotic compounds. To study the interaction between GST and toxic heavy metal ion (Hg2+), the 26 kD glutathione S-transferase from Schistosoma japonicum (Sj26GST) was expressed in Escherichia coli and purified by glutathione-sepharose affinity chromatography. The effects of Hg2+ ion on the conformation and activity of Sj26GST were studied by spectrum method and enzymatic kinetics determination, respectively. Binding of Hg2+ ion to Sj26GST produced a UV difference absorbance peak that is characteristic of ligand-to-metal charge transition (LMCT) bands and quantitative analysis indicates Sj26GST has two categories of Hg2+ ion binding sites at least. Gradual quenching of Sj26GST intrinsic fluorescence induced by Hg2+ ion was observed at the excitation wavelength of 295 nm and the quenching was of staticquenching with a quenching constant of 3.39 × 1011 mol/L-1 s-1. Far-UV and near-UV CD spectra showed that incubation of Sj26GST with Hg2+ ion resulted in slight conformational changes in either secondary or tertiary structure of Sj26GST, exhibiting a minor decrease in α-helix content and a slight increase in content of unordered coil. Enzyme activity and kinetic studies indicated Hg2+ ion inhibited Sj26GST activity in a non-competitive form. Generally speaking, the spectral data and kinetic constants indicated that the binding of Hg2+ ion induced Sj26GST to undergo a microstructural change that appears to impact on the functional conformation of the active site.